The birds of Sonora - Russell, Stephen Mims, 1931- (University of Arizona Press, 1998)
"This volume by two respected authorities covers more than 500 species of birds and contains a vast amount of information not available elsewhere. The Birds of Sonora describes all the species known from that state and includes information on distribution, seasonal patterns of occurrence, abundance, and habitats. The first book of its kind in more than half a century to treat birds of this Mexican state immediately south of Arizona, it also contains details of nesting activity for breeding species, provides insight into factors influencing distribution, and notes historical changes in status."--BOOK JACKET. "Each account is accompanied by a range map depicting the bird's range in Sonora. Drawings by internationally known wildlife artist Ray Harm enhance many of the entries."--BOOK JACKET.